A concerning condition in childhood: Hemoptysis or pseudohemoptysis? (Annals of Medical Research, 2026)
Aim: Hemoptysis is defined as expectoration of blood from the lower respiratory tract, whereas pseudohemoptysis is defined as bleeding originating from the upper airways or gastrointestinal tract. Distinguishing between these entities in children is essential because of their differing clinical implications. This study aimed to assess the diagnostic value of clinical features in differentiating hemoptysis from pseudohemoptysis in pediatric patients and to analyze the underlying causes and diagnostic approaches.Materials and Methods: A retrospective review was conducted on 94 pediatric patients who presented with oral bleeding between January 2018 and December 2024. We analyzed data on demographics, bleeding characteristics, clinical findings, diagnostic imaging, and etiologies.Results: Hemoptysis was diagnosed in 51% (n = 48) and pseudohemoptysis in 49% (n = 46) of the cases. Cough, sputum production, and pink-to-bright red blood cells were significantly associated with hemoptysis (p
Keywords: Hemoptysis; Pseudohemoptysis; Factitious hemoptysis; Child; Cough